Excess weight and factors associated in preschool of southwest of Bahia - Andressa Tavares Gomes; Taiane Gonçalves Novaes; Karine Chagas Silveira; Cláudio Lima Souza; Joel Alves Lamounier; Michele Pereira Netto; Flávio Diniz Capanema; Daniela da Silva Rocha
Abstract Objectives: this study aimed to evaluate the environmental factors associated with excess weight in preschool children. Methods: a cross-sectional study involving 664 full-time preschoolers enrolled in public childcare centers in Vitória da Conquista (BA). The excess weight status has been defined according to the BMI/Age index and score Z above +2. The independent variables were grouped into maternal characteristics, socioeconomic, related to children and child care. We conducted multiple logistic regression to assess the association between excess weight and the variables studied. Results: a prevalence of excess weight was 5.7 %; 3.9% were overweight and 1.8% were obese. The factors associated with excess weight in children were cesarean delivery (OR: 2.59; IC95%: 1.11; 6.01); being singletons (OR: 3.32; IC95%: 1.44; 7.67); and exclusive breastfeeding of less than 4 months (OR: 2.59; IC95%: 1.12; 5.99). Conclusions: the results show that interventions to reduce and/or prevent excess weight should begin prenatally, with promotion of exclusive breastfeeding and natural birth, as well as nutritional advice for mothers with singletons.